Narrative Rhetoric of Young People’s Voices to be Heard in Najwa Shihab’s Talk Show - Helen Hodiono; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2023)
The Mata Najwa (English: Najwa’s Eyes) program on October 27, 2021, entitled “Muda Bersuara” was a special episode to commemorate the Youth Pledge which fell the following day. Inviting notable guest stars from various societies, politicians, and artists, Najwa explored unsettling issues among our youths and highlighted whether or not their voices are still heard. This study was conducted because there is a widespread use of narratives on various social media platforms among youngsters but the level of literacy among them is still low. This study aimed to analyze the underlying structure of the narratives and to examine their functions. This study was done using a descriptive qualitative approach. The data analysis revealed that narratives found had a regular format in which each of them consisted of at least one structure. Every narrative was also unique and served a variety of functions with making present as its center.